Increased IgA-mediated responses to the gut paracellular pathway and blood–brain barrier proteins predict delirium due to hip fracture in older adults - Thisayakorn, Paul; Thipakorn, Yanin; Tantavisut, Saran; Sirivichayakul, Sunee; Vojdani, Aristo; Maes, Michael (Frontiers in Neurology, 2024)
Introduction Delirium is accompanied by immune response system activation, which may, in theory, cause a breakdown of the gut barrier and blood–brain barrier (BBB). Some results suggest that the BBB is compromised in delirium, but there is no data regarding the gut barrier. This study investigates whether delirium is associated with impaired BBB and gut barriers in elderly adults undergoing hip fracture surgery. Methods We recruited 59 older adults and measured peak Delirium Rating Scale (DRS) scores 2–3 days after surgery, and assessed plasma IgG/IgA levels (using ELISA techniques) for zonulin, occludin, claudin-6, β-catenin, actin (indicating damage to the gut paracellular pathway), claudin-5 and S100B (reflecting BBB damage), bacterial cytolethal distending toxin (CDT), LPS-binding protein (LBP), lipopolysaccharides (LPS), Porphyromonas gingivalis, and Helicobacter pylori. Results Results from univariate analyses showed that delirium is linked to increased IgA responses to all the self-epitopes and antigens listed above, except for LPS. Part of the variance (between 45–48.3%) in the peak DRS score measured 2–3 days post-surgery was explained by independent effects of IgA directed to LPS and LBP (or bacterial CDT), baseline DRS scores, and previous mild stroke. Increased IgA reactivity to the paracellular pathway and BBB proteins and bacterial antigens is significantly associated with the activation of M1 macrophage, T helper-1, and 17 cytokine profiles. Conclusion Heightened bacterial translocation, disruption of the tight and adherens junctions of the gut and BBB barriers, elevated CDT and LPS load in the bloodstream, and aberrations in cell–cell interactions may be risk factors for delirium.